HUBUNGAN PERBEDAAN TINGGI MUKA AIR TERHADAP KADAR Cu DAN Zn DAUN SERTA PERTUMBUHAN TANAMAN KELAPA SAWIT (Elaeis guineensis Jacq.) DI LAHAN GAMBUT - Eko Jaya Siallagan; Wawan Wawan; Nelvia Nelvia (Jurusan Tanah Fakultas Pertanian Universitas Andalas, 2021)
Peatland is an important natural resource for human life because it can be used as growth of oil palm plantation. The growth of oil palm plantations in peatlands is strongly influenced by peat water management. This study aims to study the relationship of different water levels to the content of leaf Cu and Zn nutrients and the growth of oil palm plants (Elaeis guineensis Jacq.) in the peatlands. This research has been carried out on peatland areas in oil palm plantations of PT. Jatimjaya Perkasa Sei Bangko, Kubu District, Rokan Hilir Regency, Riau Province. Analysis of soil samples and plants samples has been carried out at the Soil Laboratory, Faculty of Agriculture, Universitas Riau, Pekanbaru. The research was conducted in December 2017 to January 2018. This research was conducted using a survey method, the determination of the location of the study using a purposive sampling method, determination of sampling location is determined by stratified sampling method, where the strata in this study are grouped according to different peat water levels namely water level < 40 cm , 40 - 60 cm, and > 60 cm with oil palm plants at the same age which is six years and the piezometer has been installed properly. The parameters that observed in this study were soil pH, availability of Cu and Zn nutrient, total soil-K, content of Cu, Zn and K leaves and growth of oil palm plants which included plant height, midrib length and leaflet. The observed data were analyzed for variance and tested further by DNMRT at the level of 5%, analyzed by regression to see the relationship between water level and parameters. The results showed that peatland with water level of 40 - 60 cm had a soil pH, K-total soil, Cu leaves, Zn leaves, midrib length and the highest oil palm plantations compared to peat land with a groundwater level < 40 cm and > 60 cm, and has a different length of leaflets.Key words : Cu and Zn nutrient, Oil palm plantation, Peatlands, Water Level.